MiR-20a promotes osteogenic differentiation in bone marrow-derived mesenchymal stem/stromal cells and bone repair of the maxillary sinus defect model in rabbits - Wang, Yi-Xuan; Peng, Zhu-Li; Sun, Zhi-Wen; Pan, Yan-Jun; Ai, Hong; Mai, Zhi-Hui (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: This study aimed to determine whether miR-20 promoted osteogenic differentiation in bone marrow-derived mesenchymal stem/stromal cells (BMSCs) and accelerated bone formation in the maxillary sinus bone defect model in rabbits. Methods: BMSCs were transfected with miR-20a or anti-miR-20a for 12 h, followed by detection of RUNX2, Sp7 mRNA, bone morphogenetic protein 2 (BMP2), and RUNX2 protein expression. Alkaline phosphatase (ALP) activity and Alizarin Red S staining were used to detect calcified nodule deposition. In the rabbit maxillary sinus bone defect model, miR-20a loaded with AAV and BMP2 protein were mixed with Bio-Oss bone powder for filling the bone defect. At 4 weeks and 8 weeks, bone density was detected by cone beam computed tomography (CBCT), and new bone, osteoblasts, and collagen type 1 were evaluated by hematoxylin and eosin (HE) staining and immunohistochemical (IHC) staining. Results: Overexpression of miR-20a enhanced the mRNA and protein levels of BMP2, RUNX2, and SP7, the activity of ALP, and the levels of matrix mineralization, whereas the levels and activity of the aforementioned factors were decreased by anti-miR-20a treatment of BMSCs. Furthermore, miR-20a significantly increased the bone density, the number of osteoblasts, and the secretion of collagen type 1 in bone defects compared with Bio-Oss bone powder in the rabbit maxillary sinus bone defect model. Conclusion: Overall, miR-20a can induce osteogenic differentiation in BMSCs and accelerate bone formation of maxillary sinus defects in rabbits.